MENGGALI MAKNA DONGENG RAJA NGGOPET KE CONGKAR MASYARAKAT MANGGARAI DALAM TERANG HERMENEUTIKA PAUL RICOEUR - Gon, Videlis; Wijanar, Robertus (Universitas Hasanuddin, 2023)
This study aims to explore the meaning of one of the fairy tales originating from the Manggarai area, entitled Raja Nggopet ke Congkar. The research method used is critical discourse based on Paul Ricoeur's hermeneutical concept. This study found that this fairy tale basically explores the urgency of a critical attitude in addressing the realities of everyday life. This attitude is very important for Manggarai people in receiving and welcoming guests who come to the village. Meanwhile, for the Indonesian people in general, it is absolutely necessary to have a critical attitude in order to be able to respond wisely to the phenomena that occur in everyday life, namely: first, the phenomenon of product promotion and various other things that circulate widely on social media and in society; secondly, the phenomenon of imagery and utopian promises from legislative or executive candidates who will compete in elections.